2022
DOI: 10.1088/1742-6596/2217/1/012044
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical property analysis of shaft tubular pump rotor with different blade angle based on fluid-structure interaction

Abstract: Shaft tubular pump is widely used in large and medium-sized pumping stations with ultra-low head. But occasionally the blade cracks or even breaks, which seriously restricts the safe and stable operation of the pump station. In order to obtain the mechanical properties of the pump rotor with different blade installation angles, the fluid-structure interaction numerical simulation method is applied to analyze the structure of the pump rotor. Based on the SST k-ω model and the structured grid of the whole flow f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Yuan et al [32] simulated impellers with different structures using a single fluid-structure coupling method and found that under the same flow rate, the maximum equivalent force value of the closed impeller was the highest, while the maximum equivalent stress value of the split impeller was the lowest. Shen et al [33] considered the fluid-structure coupling effect and analyzed pump rotors with different blade installation angles. They found that under the same flow rate, the axial force increases with the increase in the blade installation angle.…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al [32] simulated impellers with different structures using a single fluid-structure coupling method and found that under the same flow rate, the maximum equivalent force value of the closed impeller was the highest, while the maximum equivalent stress value of the split impeller was the lowest. Shen et al [33] considered the fluid-structure coupling effect and analyzed pump rotors with different blade installation angles. They found that under the same flow rate, the axial force increases with the increase in the blade installation angle.…”
Section: Introductionmentioning
confidence: 99%
“…The study proved that changing the size of blade tip clearance can lead to the generation of gap leakage and leakage vortices, leading to a decrease in unit performance. Additionally, Shen Jiawei [15] conducted static and modal analyses of the pump impeller under different operating conditions using Workbench. Shi Lijian [16] studied the structural mechanical properties of full-tubular flow and axial flow pumps using fluidstructure coupling and derived the corresponding stress and strain laws.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars also analysed the cross-flow pump's internal flow and pressure pulsation characteristics, employing pressure fluctuation data [14] and vane passage frequency [15]. Others applied fluid-solid coupling [16] and finite element methods [17] to analyse the structural vibration [18] and dynamic characteristics [19]. For the inlet and outlet horn of the pump unit, scholars have carried out an optimised design to investigate the influence of the horn tube height (H) on the uniformity of the impeller inlet flow rate and the operational stability of the pump unit [20].…”
Section: Introductionmentioning
confidence: 99%